Stillbirths and neonatal deaths among 18 942 women with postpartum hemorrhage: Analysis of perinatal outcomes in the WOMAN trial. Issue 1 (2nd November 2020) - Hough, Amy; Shakur‐Still, Haleema; Roberts, Ian; Koukounari, Artemis; Lawn, Joy E.
Abstract: Objective: To describe the rates and risk factors for stillbirth and pre‐discharge neonatal mortality (PDNM), and impact on quality of life (QoL) among women with postpartum hemorrhage (PPH). Methods: A secondary analysis was conducted of the WOMAN trial, which evaluated the use of tranexamic acid for PPH and collected infant outcome data to assess drug safety. The analysis was restricted to singletons (n=18 942). Overall and country‐level rates of stillbirth and PDNM were calculated. Multilevel logistic regression models examined the association of stillbirth and PDNM with selected risks, and the association of mother's QoL at discharge after stillbirth or PDNM. Results: For women with PPH, the rate of stillbirths was 104.42 per 1000 births (n=1978) and the rate of PDNM was 15.56 per 1000 live births (n=264). Cesarean delivery, increasing blood loss, maternal complications, and maternal death were strongly associated with these adverse outcomes. Women with stillbirth and PDNM were significantly more likely to report poorer QoL. Conclusion: Women with PPH experience an extremely high rate of stillbirth and slightly elevated PDNM, which is associated with markers of the severity of their condition and impacts on their QoL. Abstract : This manuscript analyzes the huge numbers of perinatal deaths among women with postpartum hemorrhage in the WOMAN trial and the impact on quality of life.